Herbal choline as an alternative to choline chloride in the diet of nursery piglets - Letícia Lopes de Godoi; Laya Kannan Silva Alves; Ana Luísa Neves Alvarenga Dias; Hebert Silveira; Cesar Augusto Pospissil Garbossa (Pesquisa Agropecuária Brasileira, 2023)
Abstract The objective of this work was to evaluate the replacement of choline chloride supplementation by herbal choline in the diet of nursery piglets. The experimental design was randomized complete blocks (initial weight and sex) with 80 piglets, in five treatments, with eight replicates. The treatments consisted of: negative control, basal diet supplemented with 300 mg kg-1 choline via choline chloride, basal diet supplemented with 600 mg kg-1 choline via choline chloride, basal diet supplemented with 100 mg kg-1 herbal choline, and basal diet supplemented with 200 mg kg-1 herbal choline. Zootechnical performance data, blood parameters, and economic viability were analyzed. Herbal choline supplementation increases the body weight and daily feed intake of nursery piglets. The supplementation with 100 mg kg-1 herbal choline presents the highest return on investment. Herbal choline can be used as a source of choline supplementation in the diet of nursery piglets to replace choline chloride.